2018
DOI: 10.1038/s41467-018-06475-9
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-polyelectrolytes as a class of ionic macromolecules for functional materials

Abstract: The fields of soft polymers and macromolecular sciences have enjoyed a unique combination of metals and organic frameworks in the name of metallopolymers or organometallic polymers. When metallopolymers carry charged groups, they form a class of metal-containing polyelectrolytes or metallo-polyelectrolytes. This review identifies the unique properties and functions of metallo-polyelectrolytes compared with conventional organo-polyelectrolytes, in the hope of shedding light on the formation of functional materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 170 publications
(193 reference statements)
0
69
0
Order By: Relevance
“…Their properties can be adjusted by changing the interaction strength of metal centers with the polymer backbone. [44][45][46][47][48] MPs are highly interesting materials with properties combining the technological advantages of polymers with the functionality of metal centers, therefore, these compounds have outstanding potential for use in a broad range of advanced sustainable applications including functional materials, [49][50][51][52][53][54][55] catalysis and biocatalysis, [56][57][58][59][60][61][62][63] electroactive, 64 photoactive, [65][66][67][68][69][70] conducting 71 and magnetic 45 materials, as well as environment 72 and nanomaterials science. [73][74][75][76][77][78][79][80] MPs have been known for a long time but have recently become the subject of large development.…”
Section: Introductionmentioning
confidence: 99%
“…Their properties can be adjusted by changing the interaction strength of metal centers with the polymer backbone. [44][45][46][47][48] MPs are highly interesting materials with properties combining the technological advantages of polymers with the functionality of metal centers, therefore, these compounds have outstanding potential for use in a broad range of advanced sustainable applications including functional materials, [49][50][51][52][53][54][55] catalysis and biocatalysis, [56][57][58][59][60][61][62][63] electroactive, 64 photoactive, [65][66][67][68][69][70] conducting 71 and magnetic 45 materials, as well as environment 72 and nanomaterials science. [73][74][75][76][77][78][79][80] MPs have been known for a long time but have recently become the subject of large development.…”
Section: Introductionmentioning
confidence: 99%
“…Functional materials are known to be applicable in a variety of applications including energy storage devices [15], as sensors [16], as actuators [17] in water treatment [18] and in many novel electronic devices [19] for medicine, biotechnology, avionics and defense applications. Recent and old review papers have been material oriented, focusing on specific types of functional materials such as cellulosic materials [20,21], phenolics [22], graphene oxide (GO) [23], metallo-polyelectrolytes [24], carbon-based materials [25,26] and several others [27][28][29][30]. Other review papers have been more application-oriented focusing on a specific application of several functional materials including cancer therapy [31], 3D printing of devices [31], pharmaceuticals [28], photodetectors [32], wastewater treatment [33], catalysis [34] and others [35,36].…”
Section: Types Of Functional Materialsmentioning
confidence: 99%
“…For example, ferrocene has been commonly regarded as a stable "covalent" compound based on its high bond dissociation energy (BDE). [22][23][24][25] One might therefore expect ferrocene to hold little promise as a mechanophore. Very recently, however, Fromm and Weder and we independently reported that ferrocene mechanophores embedded in polymer backbones can be mechanically activated under sonication.…”
Section: Introductionmentioning
confidence: 99%